David correctly factored the expression m^2 -12m - 64.
Which expression did he write?
(1) (m - 8)(m - 8) (3) (m - 16)(m + 4)
(2) (m - 8)(m + 8) (4) (m +16)(m - 4)
Explain why

Respuesta :

Answer:

(3) (m - 16)(m + 4)

Step-by-step explanation:

Given the expression:

m^2 -12m - 64.

Using quadratic formula:

[tex] m = \frac{-b \pm \sqrt{b^2 - 4(a)(c)}}{2(a)} [/tex]

[tex] m = \frac{12 \pm \sqrt{(-12)^2 - 4(1)(-64)}}{2(1)} [/tex]

[tex] m = \frac{12 \pm 20}{2}[/tex]

[tex] m_1 = \frac{12 + 20}{2}[/tex]

[tex] m_1 = 16[/tex]

[tex] m_2 = \frac{12 - 20}{2}[/tex]

[tex] m_2 = -4[/tex]

Then, the factored expression is:

(m - 16)(m + 4)

ACCESS MORE